Sedentari Sebagai Faktor Kelebihan Berat Badan Remaja - Agus Hendra Al Rahmad (Poltekkes Kemenkes Pontianak, 2019)
Abstract: Sedentary As A Factor of Overweight At Adolescents. Currently overweight in children reaches 7,3% and increased until the year 2015 reached 9,5%. Pushes of food consumption patterns such as high consumption of fast food snacks, and lifestyle changes including sedentary suspected as a trigger factor. The study aimed to measure sedentary eﬀects on the incidence of overweight at adolescents in Banda Aceh. A case-control design study was conducted in August - September 2017 with a sample of 84 primary school children. Data were collected through interviews with parents and observations using the GPAQ questionnaire, and anthropometric measurements. Data analysis using Chi-Square and OR. The results showed that there was a signifcant correlation between excess body weight in an adolescent base (p = 0,002, OR = 4,6). In conclusion, weight gain in adolescents is due to a bad sedentary risk of 4,6 times. Suggestion, it is necessary to increase physical activity in adolescents and socialization of healthy community movement through curriculum approach in schools.Abstrak: Sedentari Sebagai Faktor Kelebihan Berat Badan Remaja. Saat ini kelebihan berat badan pada anak mencapai 7,3%, dan meningkat sampai tahun 2015 mencapai 9,5%. Pergeseran pola konsumsi pangan seperti tingginya konsumsi makanan jajanan cepat saji, dan perubahan gaya hidup termasuk sedentari lifestyle di duga sebagai faktor pemicu. Penelitian bertujuan untuk mengukur pengaruh sedentari terhadap kejadian kelebihan berat badan pada remaja di Kota Banda Aceh. Penelitian berdesain case-control yang dilakukan pada Agustus – September 2017 dengan sampel anak sekolah dasar sebanyak 84. Pengumpulan data dilakukan dengan cara wawancara terhadap orang tua murid dan observasi menggunakan kuesioner GPAQ, dilengkapi dengan pengukuran antropometri. Analisis data menggunakan Chi-Square dan OR. Hasil penelitian menunjukkan bahwa sendentari mempunyai hubungan bermakna dengan kelebihan berat badan pada remaja dasar (p= 0,002, OR= 4,6). Kesimpulan, kelebihan berat badan pada remaja disebabkan akibat sedentari tidak baik yang berisiko sebesar 4,6 kali. Saran, perlu peningkatan aktiftas fsik pada remaja serta sosialisasi gerakan masyarakat sehat melalui pendekatan kurikulum di sekolah-sekolah.